2016
DOI: 10.1021/acs.orglett.6b01716
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Co(III)/Cu(II)-Catalyzed C–N/N–N Coupling of Imidates with Anthranils: Access to 1H-Indazoles via C–H Activation

Abstract: Cooperative cobalt- and copper-catalyzed C-H activation of imidate esters and oxidative coupling with anthranils allowed efficient synthesis of 1H-indazoles in the absence of metal oxidants. The anthranil acts as a convenient aminating reagent as well as an organic oxidant in this transformation. The copper catalyst likely functions at the stage of N-N formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(54 citation statements)
references
References 81 publications
0
50
0
4
Order By: Relevance
“…The obtained KIE ( % 1.5) suggestst hat CÀHb ond cleavage might not be involved in the rate-determinings tep. Based on control experiments and previousl iterature, [14,15] ap lausible mechanism for this unifiedR h III -catalyzed straightforwards trategy is proposed for the synthesis of benzophenanthroline and benzophenanthrolinone derivatives (Scheme 7).…”
Section: Scheme5mentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained KIE ( % 1.5) suggestst hat CÀHb ond cleavage might not be involved in the rate-determinings tep. Based on control experiments and previousl iterature, [14,15] ap lausible mechanism for this unifiedR h III -catalyzed straightforwards trategy is proposed for the synthesis of benzophenanthroline and benzophenanthrolinone derivatives (Scheme 7).…”
Section: Scheme5mentioning
confidence: 99%
“…[12] Very recently,C ui's group described another Rh III -catalyzed C8-amidation of quinoline N-oxide using commercially available trifluoroacetamide. [13] Recently,b enzo[c]isoxazoles (anthranils) were highly successful as ab ifunctional arylaminating agent under redox-neutral conditions for the direct aryl amination of sp 2 and sp 3 CÀHb onds [14,15] and straightforward construction of N-PAHs. [16][17][18][19] In ar ecent report, Hashmi andc o-workers studied Au III -catalyzed construction of 2-amino pyrroles and quinoline-based polyazaheterocycles( Scheme 1a).…”
mentioning
confidence: 99%
“…Li's group established a synergistic Co III /Cu II catalyzed synthesis of indazoles 61 by the coupling of benzimiates 49 with anthranils 60 (Scheme ) . After the desired amidation of cobaltacycle with anthranil furnishes the o ‐amidation product O1 .…”
Section: Cocp* Catalyzed Annulation Reactionsmentioning
confidence: 99%
“…Other heterocyclic ring systems being synthesized using Cp*Co III catalysis include quinolines, [133a, 140] 1H-indazoles, [141] pyrroles, [142] quinazolines, [143] indolizines, [144] pyrido[2',1':2,3]pyrimido[1,6-a]indol-5-iums, [145] and2 H-chromenes. [146] In Scheme 35 it was already shown that the reactionw ith alkynes can lead to alkenylation in position-2 of indole.…”
Section: Scheme27 Aminoquinoline As Powerfuldgi Nc (Sp 3 )àHa Ctivatmentioning
confidence: 99%